Matrix-associated spatial structure contributes to compositional stability of a complex multispecies starter culture under microbial perturbation: Insights from kefir grains - Qingyang Ji; Hengxian Qu; Dawei Chen; Qiming Li; Lina Zong; Yang Liu; Yujun Huang; Ruixia Gu (Food Research International, 2026)

Unvegetated corridors nonlinearly regulate hydrological connectivity and sediment delivery in a microtidal marsh - Dawei Wang; Junhong Bai; Ken Schoutens; Jingfeng Wang; Wei Wang; Chuanhui Gu (CATENA, 2026)

Spectral feature extraction via 1D-CNN and band-synergy analysis for grassland aboveground fresh biomass estimation - Kai Gu; Jingwen Xue; Bin Bai; Xu Wang; Xiaoping Xin; Tudeng Qunpei; Sang Dan; Jinglong Wang; Dorjeeh Tondrob; Dawei Xu (Computers and Electronics in Agriculture, 2026)

A comprehensive normative atlas of cerebrovascular morphology and its associations with stroke prognosis - Yarong Ding; Longhao Cao; Zhe Wang; Dawei Li; Junyu Chen; Yong Jiang; Jing Jing; Yuesong Pan; Weibin Gu; Cang Guo; Siding Chen; Chaoyue Wang; et al. (Science Bulletin, 2026)

Arch action and beam action in reinforced engineered cementitious composite (ECC) beams subjected to shear - Dawei Gu; Yusen Zhu; Mladena Luković; Jinlong Pan (Engineering Structures, 2026)

Sodium sulfate recovery from red mud by selective de-alkalization using ferric sulfate solution and its regeneration - Zhenquan Yang; Hannian Gu; Zehai Li; Dawei Fan; Hanjie Wen (Hydrometallurgy, 2026)

Shear-tension interaction behavior and design model for ECC-embedded stud connectors - Li Xu; Bo Jiang; Jingting Lin; Dawei Gu; Jinlong Pan (Engineering Structures, 2026)

Characterization of Lactococcus lactis grx602: A novel lipase-producing probiotic strain for nutritional and sensory enhancement of sour cream - Peng Yu; Chengran Guan; Yuan Yuan; Yiping Liu; Xin Wang; Renqin Yang; Chenchen Zhang; Dawei Chen; Yujun Huang; Ruixia Gu (Food Bioscience, 2025)

Investigation on improving the high-speed performance of rotary compressor with novel axial-flow type motor rotor - Xiangqi Meng; Jingyang Li; Honghui Gu; Weijia Li; Xiangen Bai; Xiaofeng Xu; Dawei Li; Dongdong Qiao; Kai Shen; Yuejiu Zheng (International Journal of Refrigeration, 2025)

Obtaining phosphorus concentrate from phosphate ore flotation tailings after Ca and Mg recovery using formic acid leaching - Guiyong Zhou; Ning Wang; Hannian Gu; Dawei Fan; Hanjie Wen (Minerals Engineering, 2025)

Adjusting physiochemical properties of active carbon to increase its capacitive performance on the volumetric basis - Li Dawei; Li Xiaoyan; Zhu Yanjiao; Zhang Zongbo; Qu Xianfeng; Su Tong; Wei Ling; Gu Xin; Li Libin; Yan Caiwen (Desalination, 2025)

How does landscape vegetation configuration regulate local channel initiation in a rapidly expanding micro-tidal system? - Dawei Wang; Junhong Bai; Chuanhui Gu; Olivier Gourgue; Jean-Philippe Belliard; Liyue Cui; Yinghai Ke; Liming Xue; Lixiang Wen; Stijn Temmerman (Journal of Hydrology, 2025)

Understanding shear-resisting mechanism in reinforced engineered cementitious composite (ECC) beams using distributed strain measurements - Dawei Gu; Jinlong Pan; Mladena Luković (Engineering Structures, 2025)

Shear behaviour of steel-headed stud connectors in engineered cementitious composite (ECC) bridge deck under positive and negative moments - Dawei Gu; Bo Jiang; Jingting Lin; Li Xu; Jinlong Pan (Engineering Structures, 2025)

Coastal Marsh Vulnerability to Sea‐Level Rise Is Exacerbated by Plant Species Invasion - Dawei Wang; Chuanhui Gu; Stijn Temmerman; Jean‐Philippe Belliard; Olivier Gourgue; Liming Xue; Junhong Bai (Global Change Biology, 2025)
Coastal salt marshes and their valuable ecosystem services are vulnerable to degradation due to rising sea levels, to which they can adapt through biogeomorphic feedbacks. However, the invasion of plant species, particularly eco‐engineering species that alter these interactions, may degrade the structural integrity and functionality of salt marshes, potentially reducing their resilience to sea‐level rise. Such impacts presently remain poorly understood. Focusing on coastal marshes of China, we utilized a coupled biogeomorphic model to explore the effects of Spartina alterniflora invasion versus native Suaeda salsa on coastal geomorphology, considering different sea‐level rise and tidal scenarios. Our results revealed that Spartina alterniflora invasion contributed to the formation of a “levee‐basin” geomorphological structure at both the landscape scale (from seaward to landward zones) and the local scale (from channel fringes to marsh interiors). This pattern led to a prominent marsh depression, particularly in “basin” areas under microtidal conditions, indicating increased vulnerability to rising sea levels in invaded systems. Additionally, the proliferation of Spartina alterniflora could completely displace Suaeda salsa . Our findings emphasize the importance of controlling plant invasion to safeguard ecosystem resilience to environmental change.

Shear performance of perfobond leiste (PBL) connectors in engineered cementitious composites (ECC) - Dawei Gu; Jingting Lin; Bo Jiang; Huan Chen; Li Xu; Jinlong Pan (Engineering Structures, 2025)

All-in-one: Janus-structured films comprising protonated covalent organic nanosheets for adaptive all-weather personal thermal management - Guinan Chen; Yuanyuan Lou; Liangjun Chen; Tao Zhang; Yi Liang; Guangshan Zhou; Guanglun Luo; Dawei Gu; Guang Zhang; Yongwu Peng (Chemical Engineering Journal, 2025)

Improving the short-term prediction of dissolved carbon monoxide using a combination of Light GBM and meta-heuristic algorithms - Dawei Yun; Bing Zheng; Haiwei Wu; Fengrun Gu; Jiaoli Zhou (Journal of Environmental Chemical Engineering, 2024)

Screening and evaluation of a novel nucleotide-degrading Levilactobacillus brevis grx821 with anti-hyperuricemia ability - Haiying Wang; Jiaxing Dai; Yifeng Han; Yunchao Wa; Dawei Chen; Renqin Yang; Yujun Huang; Hua Wei; Ruixia Gu; Boxing Yin; Wenlong Ma (Food Bioscience, 2024)

Analysis of the changes in the absorption and regeneration performance of diethylenetriamine in carbon capture environments with functionalized alcohols and mixed amines - Lijian Jin; Xueyan Hou; Lingxiao Zhan; Dawei Hou; Lina Gu; Daguang Zhang; Jianchong Shen; Zhihao Zheng; Chao Lv; Shaoqing Liu; Linjun Yang (Fuel, 2024)

Green halochromic smart and active packaging materials based on chitosan film loading nanoparticles: Functionality, physicochemical properties and application - Liming Zhang; Dawei Yu; Yulu Gu; Yanshun Xu; Qixing Jiang; Fang Yang; Joe M. Regenstein; Dongxing Yu; Wenshui Xia (Food Hydrocolloids, 2024)

Quasi-closed-loop approach for facile and environmentally friendly red mud reutilization as advanced Li-ion anode material - Dawei Lan; Yixun Gu; Xianglong Chen; Man Mo; Zhijie Fang; Panyu Xiong; Weichi Ye; Gangli Zhao; Tianshi Xiong; Minfeng Huang; Weijian Li; Haiqing Zhan; et al. (Journal of Cleaner Production, 2024)

Effects of Nutrients on the Growth of and Free Exopolysaccharide Biosynthesis by Streptococcus thermophilus 937 in a Chemically Defined Medium - Yunchao Wa; Xia Zhao; Kuiyao Peng; Hengxian Qu; Dawei Chen; Chenchen Zhang; Xia Chen; Ruixia Gu (Current Microbiology, 2023)

An amine-modified Pd-based catalyst for highly-efficient 2-amylanthraquinone hydrogenation - Hua Yan; Xiaowei Liu; Junhong Zhou; Dawei Li; Xiaoye Yang; Yiming Gu; Hongjiu Su; Shudong Wang (Fuel, 2023)

Visual form perception predicts 3-year longitudinal development of mathematical achievement - Xinlin Zhou; Yuwei Hu; Li Yuan; Tianan Gu; Dawei Li (Cognitive Processing, 2020)

Micro-Topography Manipulations Facilitate Suaeda Salsa Marsh Restoration along the Lateral Gradient of a Tidal Creek - Dawei Wang; Junhong Bai; Wei Wang; Xu Ma; Yanan Guan; Chuanhui Gu; Shuyan Zhang; Feng Lu (Wetlands, 2020)

Study on subsidence monitoring technology using terrestrial 3D laser scanning without a target in a mining area: an example of Wangjiata coal mine, China - Yuanyuan Gu; Dawei Zhou; Demin Zhang; Kan Wu; Baohui Zhou (Bulletin of Engineering Geology and the Environment, 2020)

A Transcriptomic Analysis of Saccharomyces cerevisiae Under the Stress of 2-Phenylethanol - Danfeng Jin; Bintao Gu; Dawei Xiong; Guochang Huang; Xiaoping Huang; Lan Liu; Jun Xiao (Current Microbiology, 2018)

Design, synthesis and biological activity of N-(3-substituted-phenyl)benzenesulfonamides as selective and reversible LSD1 inhibitors - Xiaoming Zha; Liming Wu; Siyuan Xu; Fangxia Zou; Jiayue Xi; Tianfang Ma; Rongfeng Liu; Yu-Chih Liu; Dawei Deng; Yueqing Gu; Jinpei Zhou; Fei Lan (Medicinal Chemistry Research, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Comparison of cellular responses across multiple passage numbers in Ba/F3-BCR-ABL cells induced by silver nanoparticles - DaWei Guo; XiuYan Zhang; ZhiHai Huang; XueFeng Zhou; LingYing Zhu; Yun Zhao; Ning Gu (Science China Life Sciences, 2012)

The Targeting Behavior of Folate-Nanohydrogel Evaluated by Near Infrared Imaging System in Tumor-Bearing Mouse Model - Jian Zhang; Dawei Deng; Zhiyu Qian; Fei Liu; Xinyang Chen; Lianxiao An; Yueqing Gu (Pharmaceutical Research, 2010)